2010
DOI: 10.1175/2010jcli3520.1
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting Century-Scale Changes in Southern North Sea Storm Surge Climate Derived from Coupled Model Simulations

Abstract: This paper describes numerical experiments using a climate-storm surge simulation system for the coast of the United Kingdom, with a particular focus on the southern North Sea and the Thames estuary in southeastern England.Time series of surges simulated in the southern North Sea by a surge model driven by atmospheric data from a regional climate model and surges simulated by the same surge model driven by atmospheric data from a global climate model are compared. A strong correspondence is demonstrated, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 26 publications
2
49
0
Order By: Relevance
“…Nevertheless, previous studies (e.g. Sterl et al, 2009;Howard et al, 2010) have shown that it is reasonable to combine surge changes additively with mean sealevel change. Similarly Howard et al (2014) show that for their model IDSL and ADSL changes appear to be additive.…”
Section: Comparison and Addition Of Contributionsmentioning
confidence: 96%
See 1 more Smart Citation
“…Nevertheless, previous studies (e.g. Sterl et al, 2009;Howard et al, 2010) have shown that it is reasonable to combine surge changes additively with mean sealevel change. Similarly Howard et al (2014) show that for their model IDSL and ADSL changes appear to be additive.…”
Section: Comparison and Addition Of Contributionsmentioning
confidence: 96%
“…Howard et al, 2010;Sterl et al, 2009) that changes in storm surge contribution to sea level can be added linearly to mean sea-level change and so, following Lowe et al (2009), that is the approach we took in this study.…”
Section: Contribution From Srgmentioning
confidence: 99%
“…As there is sufficient evidence that the changes in extreme water level due to changes in time-mean sea-level rise and changes in storminess combine approximately linearly (e.g. Kauker and Langenberg 2000;Lowe et al 2001;Howard et al 2010) over a sizeable range of future sea levels, it is insightful to consider the two components in isolation.…”
Section: Future Changes In Extreme Sea Levelmentioning
confidence: 99%
“…van den Brink et al 2003, Sterl et al 2009) is that the surge residuals correlate with tides (when interactions exist). In contrast, skew surges do not exhibit such correlations (Howard et al 2010) and were, therefore, unsuitable for this study.…”
Section: Numerical Model Set-up and Simulation Periodmentioning
confidence: 99%
“…Horburgh and Wilson (2007) added that surges are significantly greater at low water than at high water. This interpretation was used by Howard et al (2010) to justify greater surge residuals close to low water in the Thames estuary. Surge amplification due to interactions is also sensitive to the shape and time profile of the surge such that amplification increases with decreasing surge duration (Prandle and Wolf 1978).…”
mentioning
confidence: 99%